Menstruation in sacred spaces. Medieval and early-modern Jewish women in the synagogue - Marienberg, Evyatar (Nordisk judaistik, 2004)
How sacred is the Synagogue? Can a woman enter this holy place while menstruating? What is more sacred: the space, or the Holy objects within it? In the classic sources of the Halakhah, the Jewish Law, one can find no restrictions on women from entering a synagogue while being in the state of Niddah, the state of menstrual impurity. Nevertheless, in the medieval period, more and more sources indicate that many women avoided going to the synagogue when at this state. Why? Was this custom created by women, or by men? Where did it originate? The article suggests it was the same religious mentality that pushed Jewish and Christian women to avoid going to their respective Houses of Worship while menstruating. The custom was socially problematic, as it prevented women from participating, at least passively, in the service, and from being a visible part of the community in its weekly reunion. It is suggested that in order to solve this issue, the notion of the sacrality of the synagogue was reduced to some extent in the mind of many Jewish women in the early-modern period. The Sacred was the Torah Scroll, the holiest object in the synagogue, and not so much the Synagogue itself. By doing that, women created a new viable solution: they could enter the synagogue without feeling to be transgressing its sacrality. Their respect to the Holy was shown by them avoiding looking at the Torah Scroll when it was presented to the worshippers.